Analysis of the Impact of Energy Consumption and Economic Performance on Carbon Dioxide Emissions in Indonesia Using Error Correction Mechanism - Abigail Brenda Padhang Pasorong Randa; Arlita Dwina Firlana Sari; Emily Azizaida Budikusuma; Yuniar Yudhi Tirana; Nasrudin Nasrudin (Jurnal Matematika Sains dan Teknologi, 2024)
Lately, Indonesia has been intensively developing its domestic economy. Industrial development began to be started, which attracted investors to invest. However, this massive economic development is causing an increase in CO2 emissions. This study intends to capture the effects of primary energy consumption per capita and economic performance represented by Gross Domestic Product (GDP), Foreign Direct Investment (FDI), and International Trade Openness on CO2 emissions in Indonesia from 1990–2022, in the short-run and long-run, using Error Correction Mechanisms (ECMs) analysis. In the long-run, energy consumption and GDP significantly affect CO2 emissions in Indonesia. Meanwhile, in the short-run, only energy consumption and Error Correction Term (ECT) have a significant effect on CO2 emissions. Moreover, from the ECT coefficient, it is known that the speed of adjustment to return to equilibrium is 95.08% in the first year after the shock.